Students Use English in Schoolscapes in Indonesian Highschool: Students' Perceptions - Pali'padang, Olivia Christa; Mantiri, Oktavian (8ISC Proceedings: Arts and Education, 2022)
This study aimed to find English as a Foreign Language (EFL) students' perceptions of using English in school in Indonesia. The researchers adapted the questionnaire from the modified version of (MacIntyre et al., 2001; Zarrinabadi & Abdi, 2011). This study was conducted in a private High School in Indonesia and involved 60 respondents from grade 10 of Sciences and Social Sciences, 11 of Sciences and Social Sciences, and 12 of Sciences. The result showed that the students' perceptions of English inside and outside the classroom were 2.90, moderate. Further, the findings also showed no significant difference in students' perceptions of English inside and outside the classroom based on gender since it was .262. It meant that male and female students have no different English perceptions inside and outside the classroom. Keywords : Students' Perceptions, English Usage, English in School